Effect of Diphlorethohydroxycarmalol Isolated From Ishige okamurae on Apoptosis in 3 t3‐L1 Preadipocytes. (25th September 2012) - Park, Mi Hwa; Jeon, You‐Jin; Kim, Hak‐Ju; Han, Ji Sook
<x xml:space="preserve">Abstract</x> Obesity is an important issue in the world of public health and preventive medicine. Inhibition of proliferation of preadipocytes plays an important role in proposed antiobesity mechanisms. In this study, we investigated the effect of diphlorethohydroxycarmalol (DPHC) isolated from Ishige okamurae on the apoptotic pathway. The results showed that DPHC inhibited population growth in 3 T3‐L1 preadipocytes as assessed using the 3‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyltetrazolium bromide assay. Flow cytometric analysis of 3 T3‐L1 preadipocytes showed that the number of early and late apoptotic cells increases in a dose‐dependent manner after exposure to DPHC, while the number of normal cells was reduced. Our findings indicate that the induction of apoptosis in 3 T3‐L1 preadipocytes by DPHC is mediated through the activation of caspase‐3, Bax, and caspase‐9, and then through the cleavage of poly(ADP‐ribose) polymerase and the down‐regulation of Bcl‐2. The data also indicated that treatment with DPHC inhibits histone deacetylase activity in 3 T3‐L1 preadipocytes. These results show that DPHC efficiently induces apoptosis in 3 T3‐L1 preadipocytes. Copyright © 2012 John Wiley & Sons, Ltd.